anime Pengaruh Anime (kartun Jepang) Terhadap Perilaku Kekarasan Pada Remaja: Pengaruh Anime (kartun Jepang) Terhadap Perilaku Kekarasan Pada Remaja - Nurmana, Ayyub; Florencia Irene Yuliani (UNIVERSITAS STEKOM, 2024)
Anime, a form of Japanese animation, is commonly recognized for its vibrant visuals that showcase characters in diverse settings and narratives. This unique style often emphasizes dynamic artwork and creative storytelling, distinguishing it from other forms of animation. Additionally, anime has become a cultural symbol of Japan, appealing to a wide audience both domestically and internationally due to its broad range of genres and themes. This anime is watched by various groups from children to adults based on different genres. Research on the influence of Japanese anime / cartoon on behavior aims to see the effect of Japanese anime / cartoon on violent behavior. Increased cases of violence and oppression based on cases of violence. There are those who think that exposure to violence by teenagers with shows such as anime is the cause. However, violent anime does not present scenes of events but inserts positive values that someone needs to imitate.